2018
DOI: 10.25115/ejrep.v16i46.2241
|View full text |Cite
|
Sign up to set email alerts
|

Mejora de las competencias socioemocionales en el aula, con jóvenes de Educación Secundaria, mediante el programa SEA

Abstract: Introducción. En este trabajo se presenta la evaluación del impacto de un programa de desarrollo de las competencias emo-cionales en la base del modelo teórico SEA (atención y comprensión emocional, regulación y reparación emocional y expresión social adaptativa de las emociones) sobre tales competencias en jóvenes adolescentes y pre-adolescentes.Método. El programa se implementó en un IES público durante un curso escolar por parte de los propios profesores-tutores de los alumnos. Los participantes de este est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
21

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 15 publications
0
6
0
21
Order By: Relevance
“…Some authors consider it a stable personality trait (Mavroveli et al, 2007;Mayer, Salovey, & Caruso, 2000); although different interventions and studies show that EI can be improved and trained. Studies with samples of primary secondary education students have found improvements in emotional performance after the application of intervention programs aimed at improving EI compared to the control group (Filella, Cabello, Pérez-Escoda y Ros-Morente, 2016;Ogunyemi, 2008;Rodríguez-Ledo, Orejudo, Celma & Cardoso, 2018;Schoeps et al, 2018). Similar results have also been found in samples of university students, both after the application of an intervention program (Nelis et al, 2011) and after the application of gamification programs in order to improve EI (Cejudo & Latorre, 2015).…”
Section: Introductionmentioning
confidence: 63%
“…Some authors consider it a stable personality trait (Mavroveli et al, 2007;Mayer, Salovey, & Caruso, 2000); although different interventions and studies show that EI can be improved and trained. Studies with samples of primary secondary education students have found improvements in emotional performance after the application of intervention programs aimed at improving EI compared to the control group (Filella, Cabello, Pérez-Escoda y Ros-Morente, 2016;Ogunyemi, 2008;Rodríguez-Ledo, Orejudo, Celma & Cardoso, 2018;Schoeps et al, 2018). Similar results have also been found in samples of university students, both after the application of an intervention program (Nelis et al, 2011) and after the application of gamification programs in order to improve EI (Cejudo & Latorre, 2015).…”
Section: Introductionmentioning
confidence: 63%
“…On the other hand, if we analyse the relationship between the main characteristics of the SEL programmes included in this systematic review and their effectiveness, we can see that the interventions that have been developed in out-of-school time (e.g., Santos et al, 2013;Salgado and Marques-Pinto, 2017), that employ video games (e.g., Cejudo et al, 2020) or alternative sports (e.g., Luna et al, 2019) among their procedures, practices, strategies, techniques and/or resources, with exclusively compulsory secondary education population (e.g., Castillo et al, 2013;Rodríguez-Ledo et al, 2018;Luna et al, 2019;Cejudo et al, 2020), are associated to a greater extent with a lower impact on the dependent variables considered, yielding results that are not statistically significant. Quite the opposite happens with those SEL programmes implemented in school time, as part of the curriculum, in which teachers and/or responsible external staff are trained to carry out a sequenced, active, focused, and explicit SEL training with the participating students (e.g., Milicic et al, 2013;Coelho et al, 2014Coelho et al, , 2015Coelho et al, , 2016aBerger et al, 2014;Waldemar et al, 2016;Coelho and Sousa, 2017a,b;Coelho and Sousa, 2018;Mira-Galvañ and Gilar-Corbi, 2020), as they reveal a greater impact on socioemotional competencies, well-being, and school achievement.…”
Section: Discussionmentioning
confidence: 99%
“…También se recomienda añadir a este tipo de investigaciones otros métodos de evaluación, como entrevistas, para así disponer de mayor información siendo de interés para conocer con mayor profundidad la problemática, y crear así intervenciones ajustadas. Abogamos por la necesidad de potenciar la realización de estudios mediante los que se consolide la entidad gnoseológica de la dependencia emocional y se promueva su abordaje integral, dada la multicausalidad de esta problemática (Moral y Sirvent, 2014), así como por la relevancia de la implementación de programas de optimización de recursos socioemocionales en jóvenes (véase Eslami et al, 2015;Gilar-Corbi, Pozo y Castejón, 2019;Rodríguez, Orejudo, Celma y Cardoso, 2018;Rubiales, Russo, Panieva y González, 2018).…”
Section: Discussionunclassified